Celsia coromandeliane Vahl-A New Biomarker with Immense Pharmaceutical Applications - Pal, Dilipkumar; Ahuja, Charu; Mukherjee, Souvik (Journal of Drug Delivery and Therapeutics, 2019)
Plant derived products have been important source of therapeutic agents, and now days most of the drugs are plant derived products or their derivatives. In many cases, when a plant becomes commercialized as herbal medicine, or when one of its constituents starts getting used as a pharmaceutical drug. Although herbal medicines are less potent in comparison to synthetic drugs in some cases but still these are consider less toxic or having less side effect in contrast to synthetic drugs. Objective: The present review work aims to evaluate the medicinal importance of Celsia coromandeliane Vahl. Celsia coromandeliane Vahl, is common throughout India found widely in the plains throughout India including Chhattisgarh state. Conclusion: The review of literature study suggests that, plant is found to possess various medicinal activities like antibacterial, in vitro antioxidant, anthelmintic, and CNS depressant activity. It contains sigma steroidal derivatives which has effect on puberty. Secondary metabolites present in the plant are responsible for CNS Depressant effects, Antibacterial activities, and Anthelmintic activity. Keywords: CNS Depressant effects, Antibacterial activities, Anthelmintic activity